MicroRNAs in cancer drug resistance: Basic evidence and clinical applications. Issue 3 (26th August 2018) - Ghasabi, Mehri; Mansoori, Behzad; Mohammadi, Ali; Duijf, Pascal HG; Shomali, Navid; Shirafkan, Naghmeh; Mokhtarzadeh, Ahad; Baradaran, Behzad
Abstract : Development of drug resistance has considerably limited the efficacy of cancer treatments, including chemotherapy and targeted therapies. Hence, understanding the molecular mechanisms underpinning the innate or the acquired resistance to these therapies is critical to improve drug efficiency and clinical outcomes. Several studies have implicated microRNAs (miRNA) in this process. MiRNAs repress gene expression by specific binding to complementary sequences in the 3' region of target messenger RNAs (mRNAs), followed by target mRNA degradation or blocked translation. By targeting molecules specific to a particular pathway within tumor cells, the new generation of cancer treatment strategies has shown significant advantages over conventional chemotherapy. However, the long‐term efficacy of targeted therapies often remains poor, because tumor cells develop resistance to such therapeutics. Targeted therapies often involve monoclonal antibodies (mAbs), such as those blocking the ErB/HER tyrosine kinases, epidermal growth factor receptor (cetuximab) and HER2 (trastuzumab), and those inhibiting vascular endothelial growth factor receptor signaling (e.g., bevacizumab). Even though these are among the most used agents in tumor medicine, clinical response to these drugs is reduced due to the emergence of drug resistance as a result of toxic effects in the tumor microenvironment. Research on different types of human cancers has revealed that aberrant expression of miRNAs promotes resistance to the aforementioned drugs. In this study, we review the mechanisms of tumor cell resistance to mAb therapies and the role of miRNAs therein. Emerging treatment strategies combine therapies using innovative miRNA mimics or antagonizers with conventional approaches to maximize outcomes of patients with cancer. Abstract : This literature review discuss the role of microRNAs in cancer cell resistance to targeted therapies. In addition, it discuss the molecular mechanisms underlying the development of therapeutic drug resistance based on basic evidence and clinical applications.